Analysis and Design of Secure Massive MIMO Systems in the Presence of Hardware Impairments - Zhu, Jun; Wing Kwan Ng, Derrick; Wang, Ning; Schober, Robert; Bhargava, Vijay Kishore (IEEE Transactions on Wireless Communications, 2017)
To keep the hardware costs of future communications systems manageable, the use of low-cost hardware components is desirable. This is particularly true for the emerging massive multiple-input multiple-output (MIMO) systems which equip base stations (BSs) with a large number of antenna elements. However, low-cost transceiver designs will further accentuate the hardware impairments, which are present in any practical communication system. In this paper, we investigate the impact of hardware impairments on the secrecy performance of downlink massive MIMO systems in the presence of a passive multiple-antenna eavesdropper. Thereby, for the BS and the legitimate users, the joint effects of multiplicative phase noise, additive distortion noise, and amplified receiver noise are taken into account, whereas the eavesdropper is assumed to employ ideal hardware. We derive a lower bound for the ergodic secrecy rate of a given user when matched filter data precoding and artificial noise (AN) transmission are employed at the BS. Based on the derived analytical expression, we investigate the impact of the various system parameters on the secrecy rate and optimize both the pilot sets used for uplink training and the AN precoding. Our analytical and simulation results reveal that: 1) the additive distortion noise at the BS may be beneficial for the secrecy performance, especially if the power assigned for AN emission is not sufficient; 2) all other hardware impairments have a negative impact on the secrecy performance; 3) despite their susceptibility to pilot interference in the presence of phase noise, so-called spatially orthogonal pilot sequences are preferable unless the phase noise is very strong; and 4) the proposed generalized null-space AN precoding method can efficiently mitigate the negative effects of phase noise.<br
Keywords: MIMO; Phase noise; Hardware; Distortion; Precoding; Additives; Physical layer

Multi-Objective Optimization for Robust Power Efficient and Secure Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zhu, Jun; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we investigate the power efficient resource allocation algorithm design for secure multiuser wireless communication systems employing a full-duplex (FD) base station (BS) for serving multiple half-duplex (HD) downlink (DL) and uplink (UL) users simultaneously. We propose a multi-objective optimization framework to study two conflicting yet desirable design objectives, i.e., total DL transmit power minimization and total UL transmit power minimization. To this end, the weighed Tchebycheff method is adopted to formulate the resource allocation algorithm design as a multi-objective optimization problem (MOOP). The considered MOOP takes into account the quality-of-service requirements of all legitimate users for guaranteeing secure DL and UL transmission in the presence of potential eavesdroppers. Thereby, secure UL transmission is enabled by the FD BS and would not be possible with an HD BS. The imperfectness of the channel state information of the eavesdropping channels and the inter-user interference channels is incorporated for robust resource allocation algorithm design. Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming relaxation. Simulation results not only unveil the trade-off between the total DL transmit power and the total UL transmit power, but also confirm the robustness of the proposed algorithm against potential eavesdroppers.
Keywords: Full-duplex radio; physical layer security; multi-objective optimization; non-convex optimization

Robust and Secure Resource Allocation for Full-Duplex MISO Multicarrier NOMA Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zhu, Jun; Schober, Robert (IEEE Transactions on Communications, 2018)
In this paper, we study the resource allocation algorithm design for multiple-input single-output (MISO) multicarrier non-orthogonal multiple access (MC-NOMA) systems, in which a full-duplex base station serves multiple half-duplex uplink and downlink users on the same subcarrier simultaneously. The resource allocation is optimized for maximization of the weighted system throughput while the information leakage is constrained and artificial noise is injected to guarantee secure communication in the presence of multiple potential eavesdroppers. To this end, we formulate a robust non-convex optimization problem taking into account the imperfect channel state information of the eavesdropping channels and the quality-of-service requirements of the legitimate users. Despite the non-convexity of the optimization problem, we solve it optimally by applying monotonic optimization which yields the optimal beamforming, artificial noise design, subcarrier allocation, and power allocation policy. The optimal resource allocation policy serves as a performance benchmark since the corresponding monotonic optimization-based algorithm entails a high computational complexity. Hence, we also develop a low-complexity suboptimal resource allocation algorithm which converges to a locally optimal solution. Our simulation results reveal that the performance of the suboptimal algorithm closely approaches that of the optimal algorithm. Besides, the proposed optimal MISO NOMA system can not only ensure downlink and uplink communication security simultaneously but also provides a significant system secrecy rate improvement compared with the traditional MISO orthogonal multiple access systems and two other baseline schemes.<br
Keywords: physical layer security; full-duplex radio; multicarrier systems; imperfect channel state information; Non-orthogonal multiple access (NOMA); non-convex and combinatorial optimization

Secure Downlink Transmission in Massive MIMO System with Zero-Forcing Precoding - Zhu, Jun; Bhargava, Vijay K.; Schober, Robert (European Wireless 2014; 20th European Wireless Conference, 2014)
We analyze the ergodic secrecy rate of multi-cell downlink systems assuming that the number of base station (BS) antennas per cell, the number of mobile users, and the number of eavesdropper antennas are all growing without bound. Our analysis includes the effect of uplink channel estimation, pilot contamination, and path-loss. The BS employs zero-forcing (ZF) precoding and artificial noise (AN) generation for secrecy enhancement. Our analytical results reveal that in a secure massive multiple-input multiple-output (MIMO) system employing AN, ZF precoding outperforms matched-filter (MF) precoding, unless the signal power is very small, inter-cell interference is severe, or the effect of pilot contamination is dominant.<br